The Secular as Sacred: The Historiography of the Title Page - Honey, David B. (Journal of Book of Mormon studies, 1994)
The Title Page of the Book of Mormon acts as an historiographical introduction to the editorial guidelines followed by Mormon in his work of compilation and redaction. These guidelines defined what was important for Mormon to incorporate in his historical record, and include the themes of genealogy, covenants, and the teaching and testifying of Christ.